1994
DOI: 10.1128/jb.176.19.6134-6138.1994
|View full text |Cite
|
Sign up to set email alerts
|

An Escherichia coli K-12 tktA tktB mutant deficient in transketolase activity requires pyridoxine (vitamin B6) as well as the aromatic amino acids and vitamins for growth

Abstract: We show that a tktA tktB double mutant, which is devoid of the two known transketolase isoenzymes of Escherichia coli K-12, requires pyridoxine (vitamin B6) as well as the aromatic amino acids and vitamins for growth. This pyridoxine requirement can also be satisfied by 4-hydroxy-L-threonine or glycolaldehyde. These results provide direct evidence that D-erythrose-4-phosphate is a precursor of the pyridine ring of pyridoxine.In addition, they show that the two major E. coli transketolase isoenzymes are not req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 19 publications
2
81
0
Order By: Relevance
“…This likely catalyzes the aforementioned reactions Sasajima, 1984, 1986), since other previously characterized E. coli transketolases, A and B, are not involved in deoxy-xylulose synthesis (Zhao and Winkler, 1994). Thus, CapTKT2 could be designated as a deoxyxylulose synthase, as shown for E. coli (Sprenger et al, 1997).…”
Section: The Role Of Transketolase In Generating Carbon-carbon Condenmentioning
confidence: 99%
“…This likely catalyzes the aforementioned reactions Sasajima, 1984, 1986), since other previously characterized E. coli transketolases, A and B, are not involved in deoxy-xylulose synthesis (Zhao and Winkler, 1994). Thus, CapTKT2 could be designated as a deoxyxylulose synthase, as shown for E. coli (Sprenger et al, 1997).…”
Section: The Role Of Transketolase In Generating Carbon-carbon Condenmentioning
confidence: 99%
“…SerA, and the fact that 4-hydroxy-L-threonine is struc turally related to serine, it was suggested that the pdxB gene product is erythronate-4-phosphate dehydroge nase (24). It was also revealed that serC mutant, tktA tktB double mutant and gapA epd double mutant require B6, suggesting that these genes are involved in B6 biosynthesis (23,25,26).…”
Section: Evidence From Tracer Experiments In the 1960-80smentioning
confidence: 99%
“…Biochemical approaches were also applied to prove the biosynthetic pathway proposed by Winkler (25) (Fig. 3).…”
Section: Evidence From Tracer Experiments In the 1960-80smentioning
confidence: 99%
“…This compound is thought to be der ved from 3-hydroxy-4-O-phosphoryl-2-oxobutyrate by transamination. The transaminase is encoded by pdxC(serC), a ~ene believed to be involved in both serine and 4-hydroxy-Lt lreonine biosynthesis, or its phosphorylated derivatives [3]. l~,lutants lacking a functional allele of the gene fail to synthes ze both serine and vitamin B6 [4~6].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Dempsey and c ~workers have detected phosphoserine aminotransferase ac-! vity with 3-O-phospho-e-serine as the substrate [5], evidence t)r 3-hydroxy-4-O-phosphoryl-2-oxobutyrate and 4-O-phos-1 horyl-e-threonine as intermediates in vitamin B6 formation i circumstantial [3,7]. In both transamination reactions, the ~ mino group of glutamic acid is transferred to the acceptor c~-xoacids, yielding the corresponding amino acids and a-oxolutarate ( Fig.…”
Section: Introductionmentioning
confidence: 99%